(3GdMLGRjGJ ef TYQ GdTQja GdQVjs - (3CHhGdMSf eMeO Hf GdMSjf Hf ehSi GdQVhj GdYdhj GdMSjfj GdehShjs; (3GdTQja GdQVj , CHh GdMSf eMeO Hf GdMSjf Hf ehSi GdQVj GdYdhj GdMSjfj GdehShj, CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3bGd GdSjO GdTQja GdQVj PhGdMSHjf aj GdZRd (B((3bGajI GdgeRI(B): (3Mqj Hjf GdfbG hHjf GdeUqdj hbaGJ GdQcGFH GdCfVGA s
(3BNQgG (B:s
(3bhdg(B: (3ade CQ jhe GdfaQ CcKQ VGMcG hde CQ jhe GdfaQ CcKQ HGcjG gPG BNQ GdeaQO ef ZRd TYQ GdTQja GdQVj QVj Gddg Yfg hCQVGg s
(3GdfSNI HgG MhGTs
(3HChdgG hBNQgG JbjjOGJs
(3hjhLO HChdgG JedjcGJ cKjQIs
(3hHgG JYdjbGJ s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
Keywords: (3GdCOHs